Pengalaman Auditor dan Fee Audit Dalam Meningkatkan Kualitas Audit - R Ait Novatiani; Raihan Ahmad Yunus (Owner : Riset dan Jurnal Akuntansi, 2026)
The high level of fraud in financial statements causes users of these statements to suffer losses and uncertainty  regarding company management. Therefore, high-quality audits are necessary to produce reliable financial statements.  The experience of auditors and audit fees can improve the quality of audits. The purpose of this research is to analyze auditor experience and audit fees and to examine the influence of auditor experience and audit fees  on audit quality. There were 45 respondents, consisting of 45 auditors from 32 public accounting firms in Bandung. Data collection techniques were carried out through questionnaires distributed to auditors working at public accounting firms (KAP) in Bandung. The analysis tool used in this study was multiple linear regression analysis. The results of the research prove that auditor experience, audit fees, and audit quality at Public Accounting Firms in Bandung City are good based on the results of the questionnaires processed through descriptive analysis. Auditor experience affects audit quality, and audit fees also affect audit quality.